PENGEMBANGAN BAHAN AJAR BERBASIS PROYEK PADA TEMA EKOSISTEM DI KELAS V SD - Nila Safitri; Sukmawarti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The research was conducted with the aim of developing a project-based teaching material on the theme of ecosystems that is suitable for use in the learning process of Grade V students at SD Nurhikmatika. This development research employed the ADDIE development model, which consists of five stages; however, the researcher only applied the first three stages, ending at the Development stage. The project-based teaching material on the ecosystem theme was developed using the Canva application. The validation results for the feasibility of the developed material showed that the teaching material expert gave a feasibility score of 87.6, the subject matter expert provided a score of 85, and the teacher’s response yielded a score of 88. Based on the score criteria table, the validation results from all three experts indicate that the developed project-based teaching material is classified as